Adhesive sheet

By using an adhesive sheet with a base layer containing a 10-80 μm metal layer on the internal components of the portable electronic device, and adding tackifying resin and acrylic polymer to the adhesive layer, the problem of poor shielding performance of low-frequency electromagnetic waves in the prior art is solved, and efficient low-frequency electromagnetic wave suppression and good adhesion are achieved.

CN112877004BActive Publication Date: 2025-04-01NITTO DENKO CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202011347514.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-29
Filing Date
2020-11-26
Publication Date
2025-04-01
Estimated Expiration
2040-11-26

AI Technical Summary

Technical Problem

The existing conductive adhesive tape has insufficient performance in low-frequency electromagnetic wave shielding, making it difficult to meet the demand for low-frequency electromagnetic wave suppression of portable electronic devices.

Method used

An adhesive sheet was designed, and the base layer contained a metal layer of 10 to 80 μm, with a total thickness of less than 100 μm. The electric field wave shielding effect at a frequency of 100 kHz to 1000 kHz measured by the KEC method is 20 dB or more, and the magnetic field wave shielding effect is 5 dB or more. A tackifying resin and an acrylic polymer were added to the adhesive layer to improve adhesion and weather resistance.

Benefits of technology

The electromagnetic wave shielding performance of the low-frequency area of ​​the internal components of the portable electronic equipment has been significantly improved, ensuring effective suppression of the low-frequency electromagnetic waves, while maintaining the adaptability and adhesion of the thin structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112877004B_ABST
    Figure CN112877004B_ABST
Patent Text Reader

Abstract

Provided is an adhesive sheet for fixing internal components of portable electronic devices and having excellent electromagnetic wave shielding performance in the low-frequency region. The adhesive sheet (1) comprises a substrate layer (11) and an adhesive layer (12) arranged on at least one side of the substrate layer (11). The substrate layer (11) comprises a metal layer of 10 to 80 μm. The total thickness of the adhesive sheet (1) is less than 100 μm, and the electric field wave shielding effect at a frequency of 100 kHz to 1000 kHz measured by the KEC method is greater than 20 dB, and the magnetic field wave shielding effect at a frequency of 100 kHz to 1000 kHz measured by the KEC method is greater than 5 dB. The adhesive sheet is used for fixing internal components of portable electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet, and more particularly to an adhesive sheet used for fixing internal components of portable electronic devices. Background Art

[0002] Electronic substrate components constituting electronic devices are increasingly highly integrated, and sometimes CPUs, connectors, etc. are disposed adjacent to antenna parts. In such cases, measures such as covering the CPUs, connectors, etc. with electromagnetic wave shielding materials are taken to suppress malfunctions caused by electromagnetic waves emitted by the CPUs, connectors, etc.

[0003] As such an electromagnetic wave shielding material, a conductive adhesive tape in which a conductive adhesive layer is laminated on a metal foil such as copper foil or aluminum foil can be used. Patent document 1 describes a conductive adhesive sheet having a total thickness of 30 μm or less, comprising: a conductive substrate and a conductive adhesive layer containing conductive particles, and describes: although the conductive adhesive sheet is extremely thin, it still has good adhesion and conductivity to the adherend.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2015 / 076174 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] In recent years, portable electronic devices such as smart phones have gradually become smaller and more highly integrated, and it is required to suppress the intrusion of electromagnetic waves into the interior. Furthermore, it is sometimes required to suppress the intrusion of low-frequency electromagnetic waves into portable electronic devices. However, the performance of the conductive adhesive tape disclosed in Patent Document 1 in shielding low-frequency electromagnetic waves is insufficient.

[0009] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a pressure-sensitive adhesive sheet which is used for fixing internal components of portable electronic devices and has excellent electromagnetic wave shielding performance in a low-frequency range.

[0010] Solutions for solving problems

[0011] The inventors of the present invention have conducted in-depth research to achieve the above-mentioned purpose, and found that: when using the following adhesive sheet, when used to fix the internal components of portable electronic devices, the electromagnetic wave shielding performance in the low-frequency region is excellent, the adhesive sheet has a substrate layer and an adhesive layer arranged on at least one side of the substrate layer, the substrate layer includes a metal layer of 10 to 80 μm, and the total thickness is 100 μm or less, the electric field wave shielding effect in the low-frequency region is 20 dB or more, and the magnetic field wave shielding effect is 5 dB or more. The present invention is completed based on these insights.

[0012] As one embodiment of the present invention, there is provided a pressure-sensitive adhesive sheet comprising a substrate layer and a pressure-sensitive adhesive layer provided on at least one surface of the substrate layer.

[0013] The substrate layer includes a metal layer of 10 to 80 μm.

[0014] The total thickness of the adhesive sheet is 100 μm or less,

[0015] The electric field wave shielding effect measured by the KEC method at a frequency of 100kHz to 1000kHz is 20dB or more.

[0016] The magnetic field wave shielding effect measured by the KEC method at a frequency of 100kHz to 1000kHz is 5dB or more.

[0017] The adhesive sheet is used for fixing internal components of portable electronic devices.

[0018] The adhesive sheet has a total thickness of 100 μm or less, so it is thin and suitable for fixing internal components of portable electronic devices. In addition, the substrate layer includes a metal layer, the thickness of the metal layer is 10 to 80 μm, and the electric field wave shielding effect of the adhesive sheet at a frequency of 100 kHz to 1000 kHz measured by the KEC method is 20 dB or more, and the magnetic field wave shielding effect is 5 dB or more, so it can suppress the intrusion of electromagnetic waves in the low frequency region into the interior of the portable electronic device.

[0019] The adhesive layer preferably comprises a tackifying resin and an acrylic polymer as a base polymer. By making the total thickness of the adhesive sheet less than 100 μm and the thickness of the metal layer contained in the substrate layer 10 to 80 μm, the thickness of the adhesive layer in the adhesive sheet is inevitably thinned. In particular, when the adhesive sheet is a double-sided adhesive sheet, the thickness of the adhesive layer is further thinned. However, the adhesive layer comprises a tackifying resin and an acrylic polymer as a base polymer, so that it has excellent adhesion to the internal components of the portable electronic device and is not easy to peel off.

[0020] The acrylic polymer preferably includes a structural unit derived from a carboxyl group-containing monomer and / or an acid anhydride monomer. This allows the adhesive layer to have better adhesion to internal components of a portable electronic device.

[0021] Preferably, the adhesive layer contains an azole rust inhibitor, and the content of the azole rust inhibitor is less than 8 parts by mass relative to 100 parts by mass of the total amount of the base polymer. By making the adhesive layer contain an azole rust inhibitor and using it in the above content, it is possible to suppress the corrosion of the metal that can be used as the metal layer and the internal components of the portable electronic device, and improve the cohesion (such as heat-resistant cohesion), so that the adhesion with the internal components of the portable electronic device is more excellent. The azole rust inhibitor preferably contains at least one benzotriazole compound selected from the group consisting of 1,2,3-benzotriazole, 5-methylbenzotriazole, 4-methylbenzotriazole and carboxybenzotriazole.

[0022] The ratio of the thickness of the adhesive layer to the thickness of the substrate layer [adhesive layer / substrate layer] is preferably 0.05 to 1.0. When the total thickness of the adhesive sheet is 100 μm or less, if the ratio is 0.05 or more, the adhesive layer can more fully exert its adhesive force, and the adhesion with the internal components of the portable electronic device is better. If the ratio is 1.0 or less, the thickness of the metal layer in the substrate layer is thicker, and the electromagnetic wave shielding performance in the low-frequency region is better.

[0023] The pressure-sensitive adhesive layer is preferably bonded to a metal component inside the portable electronic device.

[0024] Effects of the Invention

[0025] According to the pressure-sensitive adhesive sheet of the present invention, by being used to fix internal components of a portable electronic device, the pressure-sensitive adhesive sheet has excellent electromagnetic wave shielding performance in a low-frequency range. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram (front cross-sectional view) showing one embodiment of the pressure-sensitive adhesive sheet of the present invention.

[0027] Description of Reference Numerals

[0028] 1 Adhesive sheet

[0029] 11. Base material layer

[0030] 12 Adhesive layer DETAILED DESCRIPTION

[0031] An adhesive sheet according to one embodiment of the present invention comprises a substrate layer and an adhesive layer disposed on at least one side of the substrate layer. The adhesive sheet may be a single-sided adhesive sheet having an adhesive layer on one side of the substrate layer, or a double-sided adhesive sheet having adhesive layers on both sides of the substrate layer. The substrate layer has a metal layer.

[0032] Figure 1 Schematic cross-sectional view showing one embodiment of the adhesive sheet of the present invention. Figure 1 As shown, the pressure-sensitive adhesive sheet 1 includes a substrate layer 11 and a pressure-sensitive adhesive layer 12 provided on at least one surface of the substrate layer 11. The substrate layer 11 is, for example, a metal layer.

[0033] Examples of the metal layer include rolled metal foil, electrolytic metal foil, and other metal foils; metal vapor-deposited films, metal plated films, and the like. The metal layer may be a single layer or multiple layers. In addition, the metal layer may be composed of only one metal or may be composed of two or more metals.

[0034] The resistivity of the metal constituting the metal layer is preferably 4.0×10 -8 Ω·m or less, more preferably 3.0×10 -8 Ω·m or less. According to the above resistivity of 4.0×10 -8 There is a tendency that the metal layer composed of a metal with a resistance of Ω·m or less has a better electromagnetic wave shielding performance in a low frequency region even if it is as thin as 10 to 80 μm.

[0035] The conductivity of the metal constituting the metal layer is preferably 40% or more, more preferably 55% or more. The metal layer composed of the metal having a conductivity of 40% or more tends to have better electromagnetic wave shielding performance in the low frequency region even if it is as thin as 10 to 80 μm.

[0036] The magnetic permeability of the metal constituting the metal layer is preferably 1 or more, more preferably 200 or more, further preferably 230 or more, and particularly preferably 280 or more, when copper is set to 1. The metal layer composed of the metal having a magnetic permeability of 1 or more tends to have better electromagnetic wave shielding performance in the low-frequency region even if it is as thin as 10 to 80 μm.

[0037] It is particularly preferred that the metal constituting the metal layer satisfies at least one of the electrical conductivity being within the above range and the magnetic permeability being within the above range.

[0038] As the metal constituting the above-mentioned metal layer, gold, silver, copper, aluminum, iron and alloys containing one or more of these are preferred. Even if the metal layer composed of the above-mentioned metal is as thin as 10 to 80 μm, there is a tendency that the electromagnetic wave shielding performance in the low-frequency region is better. From the viewpoint of better electromagnetic wave shielding performance in the low-frequency region, copper layers, silver layers, aluminum layers, and iron layers are preferred, and from the viewpoint of economic efficiency, copper layers are preferred.

[0039] The thickness of the metal layer is 10 to 80 μm, preferably 10 to 60 μm. In particular, when the metal layer is a copper layer or a silver layer, it is preferably 30 to 60 μm. When the metal layer is an aluminum layer, it is preferably 10 to 30 μm. When the metal layer is an iron layer, it is preferably 40 to 70 μm.

[0040] The above-mentioned substrate layer may be laminated with other substrates except the above-mentioned metal layer. As the above-mentioned other substrates, various optical films such as plastic films, anti-reflection (AR) films, polarizing plates, phase difference plates, etc. can be listed. In addition, as the above-mentioned other substrates, porous materials such as paper, cloth, non-woven fabrics, meshes, foam sheets, etc. can be listed. As raw materials for the above-mentioned plastic films, polyester resins such as polyethylene terephthalate (PET) can be listed; acrylic resins such as polymethyl methacrylate (PMMA); polycarbonate, cellulose triacetate (TAC), polysulfone, polyarylate, polyimide, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymer, trade name "ARTON" (cyclic olefin polymer, JSR company), trade name "ZEONOR" (cyclic olefin polymer, Japan ZEON company system) and other cyclic olefin polymers and other plastic materials. It should be noted that these plastic materials can be used only one, or two or more can be used. In addition, in this specification, the above-mentioned other base material does not include a separator (release liner) which is peeled off when using (sticking) the pressure-sensitive adhesive sheet.

[0041] In addition, for the purpose of improving the adhesion and retention of the adhesive layer, the adhesive layer side surface of the substrate layer may be subjected to physical treatments such as corona discharge treatment, plasma treatment, sandblasting treatment, ozone exposure treatment, flame exposure treatment, high voltage electric shock exposure treatment, ionizing radiation treatment, etc.; chemical treatments such as chromic acid treatment; and surface treatments such as easy adhesion treatment based on a coating agent (primer). The surface treatment for improving adhesion is preferably applied to the entire surface of the adhesive layer side of the substrate layer.

[0042] As the adhesive constituting the above-mentioned adhesive layer, there is no particular limitation, and examples thereof include acrylic adhesives, rubber adhesives (natural rubber, synthetic rubber, mixed systems thereof, etc.), silicone adhesives, polyester adhesives, urethane adhesives, polyether adhesives, polyamide adhesives, fluorine adhesives, etc. Among them, as the adhesive constituting the adhesive layer, from the viewpoint of transparency, adhesion, weather resistance, cost, and ease of design of the adhesive, acrylic adhesives are preferably used. The above-mentioned adhesive layer is preferably an acrylic adhesive layer consisting of an acrylic adhesive. The above-mentioned adhesive can be used only one, or two or more.

[0043] The acrylic adhesive layer contains an acrylic polymer as a base polymer. The acrylic polymer is a polymer containing an acrylic monomer (a monomer having a (meth)acryloyl group in the molecule) as a monomer component constituting the polymer. That is, the acrylic polymer contains a structural unit derived from an acrylic monomer. The acrylic polymer is preferably a polymer containing an alkyl (meth)acrylate as a monomer component constituting the polymer. It should be noted that only one type of acrylic polymer may be used, or two or more types may be used.

[0044] It should be noted that in the present specification, the base polymer refers to the main component of the polymer components used in the adhesive layer, for example, a polymer component whose content exceeds 50% by mass. The acrylic adhesive layer may be an adhesive layer substantially composed of an acrylic polymer, wherein the content of the acrylic polymer in the acrylic adhesive layer is preferably 70% by mass or more, more preferably 90% by mass or more, and further preferably more than 98% by mass, relative to 100% by mass of the total amount of the acrylic adhesive layer.

[0045] The acrylic polymer is preferably a polymer composed (formed) of an alkyl (meth)acrylate as an essential monomer component. That is, the acrylic polymer preferably contains an alkyl (meth)acrylate as a structural unit. It should be noted that in this specification, "(meth)acrylic" means "acrylic" and / or "methacrylic" (either or both of "acrylic" and "methacrylic"), and the same applies to the others.

[0046] As the alkyl (meth)acrylate which is an essential monomer component, preferably, there are alkyl (meth)acrylates having a linear alkyl group or a branched alkyl group. The alkyl (meth)acrylates may be used alone or in combination of two or more.

[0047] The (meth)acrylic acid alkyl ester having a linear or branched alkyl group is not particularly limited, and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, propyl ... tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate, tert-butyl (meth)acrylate Alkyl (meth)acrylates having a linear or branched alkyl group having 1 to 20 carbon atoms, such as isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate (stearyl (meth)acrylate), isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among them, the alkyl (meth)acrylate having a linear or branched alkyl group is preferably an alkyl (meth)acrylate having a linear or branched alkyl group having 1 to 18 carbon atoms (particularly 2 to 4), and butyl (meth)acrylate (BA) is more preferred from the viewpoint of being able to form an adhesive layer having good adhesion even if it is thin.

[0048] The proportion of the above-mentioned alkyl (meth)acrylate in the total amount 100% by mass of all monomer components constituting the above-mentioned acrylic polymer is not particularly limited, and is preferably 50% by mass or more (e.g., 50 to 100% by mass), more preferably 70% by mass or more, further preferably 85% by mass or more, and particularly preferably 90% by mass or more. The above-mentioned proportion is preferably less than 100% by mass, more preferably 99.5% by mass or less, further preferably 98% by mass or less, and particularly preferably 97% by mass or less. If the above-mentioned proportion is within the above-mentioned range, the balance with the amount of the copolymerizable monomer is good, and an adhesive layer with good adhesion can be formed even if it is thin.

[0049] The acrylic polymer may contain a copolymerizable monomer together with the (meth)acrylic acid alkyl ester as a monomer component constituting the polymer. That is, the acrylic polymer may contain a copolymerizable monomer as a structural unit. The copolymerizable monomer may be used alone or in combination of two or more.

[0050] As the copolymerizable monomer, from the viewpoint of being able to form an adhesive layer with good adhesion even if it is thin, preferably a carboxyl-containing monomer and / or anhydride monomer. As the carboxyl-containing monomer, for example, acrylic acid, methacrylic acid, (meth) carboxyethyl acrylate, (meth) carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. can be listed. As the anhydride monomer, for example, maleic anhydride, itaconic anhydride, etc. can be listed.

[0051] The proportion of the carboxyl-containing monomer and / or anhydride monomer in the total amount of all monomer components 100% by mass constituting the acrylic polymer is not particularly limited, and is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, further preferably 1% by mass or more, particularly preferably 2% by mass or more, and can be 3% by mass or more, 3.2% by mass or more, 3.5% by mass or more, 4% by mass or more, or 4.5% by mass or more. The above proportion is preferably 15% by mass or less, more preferably 12% by mass or less, further preferably 10% by mass or less, particularly preferably 7% by mass or less, and can be less than 7% by mass, 6.8% by mass or less, or 6% by mass or less. If the above proportion is within the above range, the balance with the amount of the (meth) alkyl acrylate is good, and an adhesive layer with good adhesion can be formed even if it is thin.

[0052] The copolymerizable monomer may contain a functional group-containing monomer for the purpose of further introducing crosslinking points into the acrylic polymer or improving the cohesive force of the acrylic polymer. Examples of the functional group-containing monomer include hydroxyl-containing monomers, epoxy-containing monomers, nitrogen-containing monomers, ketone-containing monomers, alkoxysilyl-containing monomers, sulfonic acid-containing monomers, and phosphoric acid-containing monomers.

[0053] Examples of the hydroxyl-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate; unsaturated alcohols such as vinyl alcohol and allyl alcohol; and polypropylene glycol mono(meth)acrylate.

[0054] Examples of the epoxy group-containing monomer include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether, and the like.

[0055] Examples of the nitrogen-containing monomers include amide-containing monomers, amino-containing monomers, cyano-containing monomers, and monomers having a nitrogen-containing ring. Examples of the amide-containing monomers include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide, N-methoxymethyl(meth)acrylamide, and N-butoxymethyl(meth)acrylamide. Examples of the amino-containing monomers include aminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, and tert-butylaminoethyl(meth)acrylate. Examples of the cyano-containing monomers include acrylonitrile and methacrylonitrile. Examples of the monomer having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, and N-(methyl)acryloylmorpholine.

[0056] Examples of the ketone group-containing monomer include diacetone (meth)acrylamide, diacetone (meth)acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, and vinyl acetoacetate.

[0057] Examples of the alkoxysilyl group-containing monomer include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane.

[0058] Examples of the sulfonic acid group-containing monomer include styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl(meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid.

[0059] As said phosphoric acid group-containing monomer, 2-hydroxyethyl acryloyl phosphate etc. are mentioned, for example.

[0060] The proportion of the above-mentioned functional group-containing monomer in the total amount 100% by mass of all monomer components constituting the above-mentioned acrylic polymer can be, for example, 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more. The above-mentioned proportion can be, for example, 40% by mass or less, 20% by mass or less, 10% by mass or less, or 5% by mass or less, and may be substantially free of the monomer. It should be noted that, in this specification, substantially free of the monomer means that the monomer is included non-subjectively, such as in the case of inevitable mixing, without active compounding, and is, for example, 0.05% by mass or less, or 0.01% by mass or less.

[0061] The copolymerizable monomer may further contain other monomers. Examples of the other monomers include vinyl ester monomers such as vinyl acetate, vinyl propionate, and vinyl laurate; aromatic vinyl compounds such as styrene, substituted styrenes (such as α-methylstyrene), and vinyltoluene; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylates containing aromatic rings such as aryl (meth)acrylates (such as phenyl (meth)acrylate), aryloxyalkyl (meth)acrylates (such as phenoxyethyl (meth)acrylate), and arylalkyl (meth)acrylates (such as benzyl (meth)acrylate); olefin monomers such as ethylene, propylene, isoprene, butadiene, and isobutylene; chlorine-containing monomers such as vinyl chloride and vinylidene chloride; isocyanate group-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate; alkoxy group-containing monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; and vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether.

[0062] The proportion of the above-mentioned other monomers in the total amount 100 mass % of all monomer components constituting the above-mentioned acrylic polymer can be, for example, 0.05 mass % or more, 0.5 mass % or more, for example, 20 mass % or less, 10 mass % or less, 5 mass % or less, and may be substantially absent.

[0063] In the acrylic polymer, in order to form a cross-linked structure in its polymer skeleton, as a monomer component constituting the polymer, a multifunctional monomer that can be copolymerized with the monomer component forming the acrylic polymer can be included. As the multifunctional monomer, for example, hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy (meth)acrylate (for example, poly(meth)acrylate glycidyl), polyester (meth)acrylate, urethane (meth)acrylate, etc., monomers having (meth)acryloyl groups and other reactive functional groups in the molecule, etc. can be listed. The multifunctional monomer can be used alone or in combination of two or more. It should be noted that the above-mentioned multifunctional monomers exhibit the same function as the cross-linking agent described below and also belong to the cross-linking agent.

[0064] The Tg of the acrylic polymer is not particularly limited, but is preferably below -15°C, more preferably below -25°C, further preferably below -35°C, and particularly preferably below -40°C. In addition, the Tg is preferably above -70°C, more preferably above -65°C, further preferably above -60°C, and particularly preferably above -55°C. If the Tg is within the above range, there is a tendency that an adhesive layer having good adhesion can be formed even if it is thin. The Tg of the acrylic polymer is a theoretical value calculated based on the Fox formula.

[0065] As the glass transition temperature of the homopolymer used for calculating Tg, the value described in the known document is used. For example, for the monomers listed below, the following values ​​are used as the glass transition temperature of the homopolymer of the monomer.

[0066]

[0067] For the glass transition temperature of the homopolymer of the monomers other than those exemplified above, the values ​​recorded in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc, 1989) are used. It should be noted that for monomers for which multiple values ​​are recorded in this document, the highest value is adopted. In the case where there is no record in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc, 1989), the value obtained by the following measurement method is used (refer to Japanese Patent Publication No. 2007-51271).

[0068] Specifically, 100 parts by mass of monomer, 0.2 parts by mass of azobisisobutyronitrile and 200 parts by mass of ethyl acetate as a polymerization solvent were added to a reactor equipped with a thermometer, a stirrer, a nitrogen inlet pipe and a reflux condenser, and stirred for 1 hour while circulating nitrogen. After removing oxygen in the polymerization system by such operation, the temperature was raised to 63°C and reacted for 10 hours. Then, it was cooled to room temperature to obtain a homopolymer solution having a solid content concentration of 33% by mass. Then, the homopolymer solution was cast on a release liner and dried to prepare a test sample (sheet-shaped homopolymer) having a thickness of about 2 mm. The test sample was punched into a disc with a diameter of 7.9 mm and clamped between parallel plates. A viscoelasticity tester (trade name "ARES", manufactured by Leometrics) was used to apply shear strain at a frequency of 1 Hz. The viscoelasticity was measured using a shear mode in a temperature range of -70 to 150°C and a heating rate of 5°C / min. The peak temperature of tanδ (loss tangent) was taken as the Tg of the homopolymer.

[0069] The weight average molecular weight of the acrylic polymer is preferably 100,000 to 5,000,000, more preferably 300,000 to 2,000,000, further preferably 450,000 to 1,500,000, further preferably 450,000 to 1,500,000, and particularly preferably 650,000 to 1,300,000. The weight average molecular weight is a value measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.

[0070] The base polymer such as the acrylic polymer contained in the adhesive layer is obtained by polymerizing the monomer components. The polymerization method is not particularly limited, and examples thereof include solution polymerization, emulsion polymerization, bulk polymerization, and polymerization methods based on active energy ray irradiation (active energy ray polymerization methods). Among them, from the perspectives of transparency and cost of the adhesive layer, solution polymerization and active energy ray polymerization are preferred, and solution polymerization is more preferred.

[0071] In addition, various general solvents can be used in the polymerization of the above-mentioned monomer components. Examples of the above-mentioned solvents include esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; ketones such as methyl ethyl ketone and methyl isobutyl ketone, and other organic solvents. It should be noted that only one solvent may be used, or two or more solvents may be used.

[0072] When the monomer components are polymerized, a polymerization initiator such as a thermal polymerization initiator or a photopolymerization initiator (photoinitiator) may be used depending on the type of polymerization reaction. It should be noted that the polymerization initiator may be used alone or in combination of two or more.

[0073] As the above-mentioned thermal polymerization initiator, there is no particular limitation, and examples thereof include azo-based polymerization initiators, peroxide-based polymerization initiators (e.g., dibenzoyl peroxide, tert-butyl permaleate, persulfates such as potassium persulfate, benzoyl peroxide, hydrogen peroxide, etc.), substituted ethane-based initiators such as phenyl-substituted ethane, aromatic carbonyl compounds, redox-based polymerization initiators, etc. Among them, the azo-based polymerization initiators disclosed in Japanese Patent Application Laid-Open No. 2002-69411 are preferred. As the above-mentioned azo-based polymerization initiators, 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as "AIBN"), 2,2'-azobis-2-methylbutyronitrile (hereinafter sometimes referred to as "AMBN"), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis-4-cyanovaleric acid, etc. can be listed. The amount of the thermal polymerization initiator used may be a common amount, and can be selected from the range of, for example, 0.005 to 1 part by mass, preferably 0.01 to 1 part by mass, based on 100 parts by mass of the monomer component.

[0074] The photopolymerization initiator is not particularly limited, and examples thereof include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators. In addition, acylphosphine oxide-based photopolymerization initiators and titanocene-based photopolymerization initiators can also be listed. Examples of the benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of the acetophenone-based photopolymerization initiator include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of the α-ketol-based photopolymerization initiator include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of the aromatic sulfonyl chloride-based photopolymerization initiator include 2-naphthalenesulfonyl chloride. Examples of the photoactive oxime-based photopolymerization initiator include 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl)-oxime. Examples of the benzoin-based photopolymerization initiator include benzoin. Examples of the benzyl-based photopolymerization initiator include benzyl. As the above-mentioned benzophenone-based photopolymerization initiator, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, etc. can be listed. As the above-mentioned ketal-based photopolymerization initiator, for example, benzildimethylketal, etc. can be listed. As the above-mentioned thioxanthone-based photopolymerization initiator, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, etc. can be listed. As the above-mentioned acylphosphine oxide-based photopolymerization initiator, for example, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, etc. can be listed. As the above-mentioned titanocene-based photopolymerization initiator, for example, bis(η 5 -2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, etc. The amount of the photopolymerization initiator used can be a common amount, for example, it can be selected from the range of 0.01 to 3 parts by mass, preferably 0.1 to 1.5 parts by mass, relative to 100 parts by mass of the monomer component.

[0075] The adhesive layer preferably contains a tackifying resin. If the tackifying resin is contained, the adhesive layer tends to have better adhesion even if it is thin. By making the total thickness of the adhesive sheet less than 100 μm and the thickness of the metal layer contained in the substrate layer 10 to 80 μm, the thickness of the adhesive layer in the adhesive sheet is inevitably thinned. In particular, when the adhesive sheet is a double-sided adhesive sheet, the thickness of the adhesive layer is further thinned. However, the adhesive layer contains a tackifying resin and an acrylic polymer as a base polymer, so that it has excellent adhesion to the internal components of the portable electronic device and is difficult to peel off.

[0076] As the above-mentioned tackifying resin, for example, phenolic tackifying resin, terpene tackifying resin, rosin tackifying resin, hydrocarbon tackifying resin, epoxy tackifying resin, polyamide tackifying resin, elastic system tackifying resin, ketone tackifying resin, etc. can be listed. In addition, as the above-mentioned tackifying resin, in addition to this, oligomers of (meth) alkyl acrylates such as oligomers of dicyclopentyl methacrylate (DCPMA) and methyl methacrylate (MMA) can also be listed. The above-mentioned tackifying resin can be used alone or in combination of two or more.

[0077] As the above-mentioned phenolic tackifying resin, terpene phenol resin, hydrogenated terpene phenol resin, alkylphenol-formaldehyde resin, rosin phenol-formaldehyde resin can be listed. The above-mentioned terpene phenol resin is a polymer containing terpene residues and phenol residues, and copolymers of terpenes and phenol compounds (terpene-phenol copolymer resins) and products obtained by phenol-modified homopolymers or copolymers of terpenes (phenol-modified terpene resins) can be listed. As terpenes constituting the above-mentioned terpene phenol resin, monoterpenes such as α-pinene, β-pinene, limonene (d-isomer, l-isomer, d / l-isomer (dipentene) etc.) can be listed. The above-mentioned hydrogenated terpene phenol resin is a resin having a structure obtained by hydrogenating the above-mentioned terpene phenol resin. The above-mentioned alkylphenol-formaldehyde resin is a resin obtained from alkylphenol and formaldehyde (oily phenol-formaldehyde resin). As the above-mentioned alkylphenol-formaldehyde resin, for example, novolac type and resol type resins can be listed. The rosin phenolic resin is a phenol-modified product of rosin or various rosin derivatives described below. The rosin phenolic resin can be obtained, for example, by adding phenol to rosin or various rosin derivatives described below using an acid catalyst and performing thermal polymerization.

[0078] As the above-mentioned terpene-based tackifying resin, polymers of terpenes (typically, monoterpenes) such as α-pinene, β-pinene, d-limonene, l-limonene, and dipentene can be listed. The above-mentioned terpene polymer can be a homopolymer of one terpene, or a copolymer of two or more terpenes. As a homopolymer of a terpene, α-pinene polymer, β-pinene polymer, dipentene polymer, etc. can be listed. The above-mentioned modified terpene-based tackifying resin can be a resin obtained by modifying the above-mentioned terpene resin (modified terpene resin). As the above-mentioned modified terpene resin, styrene-modified terpene resin, hydrogenated terpene resin, etc. can be listed.

[0079] Examples of the rosin-based tackifying resin include rosins and rosin derivative resins. Examples of the rosins include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; and modified rosins (hydrogenated rosin, disproportionated rosin, polymerized rosin, and other chemically modified rosins) obtained by modifying these unmodified rosins by hydrogenation, disproportionation, and polymerization. Examples of the rosin derivative resin include derivatives of the rosins. Examples of the rosin derivative resin include rosin esters such as unmodified rosin esters (esters of unmodified rosin and alcohols), modified rosin esters (esters of modified rosin and alcohols), unsaturated fatty acid-modified rosins obtained by modifying rosin with unsaturated fatty acids, unsaturated fatty acid-modified rosin esters obtained by modifying rosin esters with unsaturated fatty acids, rosin alcohols obtained by reducing the carboxyl groups of rosin or the above-mentioned various rosin derivatives, and metal salts of rosin or the above-mentioned various rosin derivatives. Specific examples of the rosin esters include methyl esters, triethylene glycol esters, glycerol esters, pentaerythritol esters, and the like of unmodified rosin or modified rosin.

[0080] Examples of the hydrocarbon tackifying resins include aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aliphatic / aromatic petroleum resins (styrene-olefin copolymers, etc.), aliphatic / alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, and coumarone indene resins.

[0081] The softening point (softening temperature) of the above-mentioned tackifying resin is not particularly limited, and is preferably above 80°C, more preferably above 100°C, further preferably above 135°C, and particularly preferably above 140°C. If a tackifying resin having a softening point of above 80°C (especially above 135°C) is used, an adhesive layer having better adhesion can be formed even if it is thin. From the viewpoint of improving the adhesion to the adherend, the above-mentioned softening point is, for example, below 200°C, preferably below 180°C. In particular, the above-mentioned terpene phenol tackifying resin having a softening point within the above-mentioned range is preferred. It should be noted that the softening point of the tackifying resin can be measured based on the softening point test method (ring and ball method) specified in JIS K2207.

[0082] The hydroxyl value of the above-mentioned tackifying resin is not particularly limited, preferably more than 20mgKOH / g, more preferably more than 30mgKOH / g, more preferably more than 50mgKOH / g, particularly preferably more than 70mgKOH / g. If the above-mentioned hydroxyl value is more than 20mgKOH / g (especially more than 70mgKOH / g), then even if thin, an adhesive layer with more excellent adhesion can be formed. The above-mentioned hydroxyl value is, for example, less than 200mgKOH / g, preferably less than 180mgKOH / g, more preferably less than 160mgKOH / g, and more preferably less than 140mgKOH / g. In particular, the above-mentioned terpene phenol tackifying resin with the above-mentioned hydroxyl value in the above-mentioned range is preferred. It should be noted that the hydroxyl value of the tackifying resin can be measured by the potentiometric titration method specified in JIS K0070:1992.

[0083] The content of the above-mentioned tackifying resin in the above-mentioned adhesive layer is not particularly limited, and is, for example, 1 part by mass or more (for example, 1 to 100 parts by mass), preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 15 parts by mass or more, relative to the total amount of 100 parts by mass of the above-mentioned base polymer. If the above-mentioned content is 1 part by mass or more, the adhesive layer has better adhesion even if it is thin. From the viewpoint of excellent heat-resistant cohesion, the above-mentioned content is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and further preferably 30 parts by mass or less. In particular, the content of the above-mentioned terpene-phenol tackifying resin (especially the above-mentioned terpene-phenol tackifying resin having a softening point within the above-mentioned range) is preferably within the above-mentioned range.

[0084] The adhesive layer preferably contains a rust inhibitor. As mentioned above, the acrylic polymer in the acrylic adhesive preferably contains a carboxyl group-containing monomer and / or anhydride monomer as a copolymerizable monomer. However, the carboxyl group-containing monomer and anhydride monomer that may remain in the adhesive layer may cause the metal that can be used as the internal components of the above-mentioned metal layer and portable electronic devices to be corroded. Therefore, the above-mentioned corrosion can be suppressed by mixing a rust inhibitor. The above-mentioned rust inhibitor can be used alone or in combination of two or more.

[0085] Examples of the rust inhibitor include amine-based rust inhibitors, azole-based rust inhibitors, and nitrite-based rust inhibitors. In addition, examples include ammonium benzoate, ammonium phthalate, ammonium stearate, ammonium palmitate, ammonium oleate, ammonium carbonate, dicyclohexylamine benzoate, urea, hexamethylenetetramine, thiourea, phenyl carbamate, and cyclohexylammonium-N-cyclohexylcarbamate (CHC).

[0086] As the above-mentioned rust inhibitor, preferably an azole-based rust inhibitor. It is possible to suppress the corrosion of the metal used as the above-mentioned metal layer and the internal components of the portable electronic device, and improve the cohesion (such as heat-resistant cohesion), so that the adhesion with the internal components of the portable electronic device is more excellent. In particular, by combining an isocyanate-based cross-linking agent and other cross-linking agents in the composition containing the azole-based rust inhibitor, it is possible to preferably take into account both the cohesion (such as heat-resistant cohesion) and the anti-metal corrosion property.

[0087] As the azole-based rust inhibitor, it is preferred that an azole-based compound which is a five-membered aromatic compound containing two or more hetero atoms and at least one of the hetero atoms is a nitrogen atom is used as an active ingredient.

[0088] Examples of the azole compounds include imidazole, pyrazole, oxazole, isoxazole, thiazole, isothiazole, selenazole, 1,2,3-triazole, 1,2,4-triazole, 1,2,5-oxadiazole, 1,3,4-oxadiazole, 1,2,3-thiadiazole, 1,2,4-thiadiazole, 1,3,4-thiadiazole, tetrazole, 1,2,3,4-thiatriazole, and the like; derivatives thereof; amine salts thereof; metal salts thereof, and the like. Examples of the derivatives of the azoles include compounds having a condensed ring structure of an azole ring and another ring (e.g., a benzene ring). Specific examples include indazole, benzimidazole, benzotriazole (i.e., 1,2,3-benzotriazole in which the azole ring of 1,2,3-triazole is fused with a benzene ring), benzothiazole, and their derivatives such as alkylbenzotriazoles (e.g., 5-methylbenzotriazole, 5-ethylbenzotriazole, 5-n-propylbenzotriazole, 5-isobutylbenzotriazole, 4-methylbenzotriazole), alkoxybenzotriazoles (e.g., 5-methoxybenzotriazole), alkylaminobenzotriazoles, and the like. Triazole, alkylaminosulfonylbenzotriazole, mercaptobenzotriazole, hydroxybenzotriazole, nitrobenzotriazole (e.g., 4-nitrobenzotriazole), halogenated benzotriazole (e.g., 5-chlorobenzotriazole), hydroxyalkylbenzotriazole, hydroxybenzotriazole, aminobenzotriazole, (substituted aminomethyl)tolyltriazole, carboxybenzotriazole, N-alkylbenzotriazole, bisbenzotriazole, naphthotriazole, mercaptobenzothiazole, aminobenzothiazole, etc., amine salts thereof, metal salts thereof, etc. Other examples of azole derivatives include azole derivatives of non-condensed ring structures, for example, compounds having a structure having a substituent on a non-condensed azole ring such as 3-amino-1,2,4-triazole and 5-phenyl-1H-tetrazole.

[0089] The azole compound is preferably a benzotriazole compound. The benzotriazole compound is a compound having a benzotriazole skeleton, and is preferably a compound represented by the following formula (1) from the viewpoint of being able to further suppress metal corrosion.

[0090]

[0091] In the above formula (1), R 1 The substituents include, for example, alkyl groups having 1 to 6 carbon atoms, alkoxy groups having 1 to 6 carbon atoms, aryl groups having 6 to 14 carbon atoms, carboxyl groups, carboxylalkyl groups having 2 to 6 carbon atoms, amino groups, mono- or di-C 1-10 Alkylamino, amino C 1-6 Alkyl, mono- or di-C 1-10 Alkylamino-C 1-6 Alkyl, mercapto, alkoxycarbonyl having 1 to 6 carbon atoms, etc.

[0092] In the above formula (1), n ​​is an integer of 0 to 4. When n is an integer of 2 or more, the n R 1 They are optionally the same as or different from each other.

[0093] In the above formula (1), R 2 Examples include a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 14 carbon atoms, an amino group, a mono- or di-C 1-10 Alkylamino, amino C 1-6 Alkyl, mono- or di-C 1-10 Alkylamino-C 1-6 Alkyl, mercapto, alkoxycarbonyl having 1 to 12 carbon atoms, etc. 1 With R 2 Optional same or different.

[0094] As the compound represented by the above formula (1), 1,2,3-benzotriazole, 5-methylbenzotriazole, 4-methylbenzotriazole and carboxybenzotriazole are preferred.

[0095] Examples of the amine-based rust inhibitors include hydroxyl-containing amine compounds such as 2-amino-2-methyl-1-propanol, monoethanolamine, monoisopropanolamine, diethylethanolamine, ammonia, and ammonia water; cyclic amines such as morpholine; cyclic alkylamine compounds such as cyclohexylamine; and linear alkylamines such as 3-methoxypropylamine. Examples of the nitrite-based rust inhibitors include dicyclohexyl ammonium nitrite (DICHAN), diisopropyl ammonium nitrite (DIPAN), sodium nitrite, potassium nitrite, and calcium nitrite.

[0096] The content of the above-mentioned rust inhibitor in the above-mentioned adhesive layer is not particularly limited. From the viewpoint that the corrosion resistance of the metal is more excellent, relative to the total amount of 100 mass parts of the above-mentioned base polymer, it is preferably more than 0.01 mass parts, more preferably more than 0.05 mass parts, more preferably more than 0.1 mass parts, more preferably more than 0.3 mass parts, and particularly preferably more than 0.5 mass parts. In addition, the above-mentioned content is preferably less than 8 mass parts, more preferably less than 6 mass parts, and more preferably less than 5 mass parts. In particular, the content of the above-mentioned azole rust inhibitor is preferably within the above-mentioned range. By using the above-mentioned azole rust inhibitor with the above-mentioned content, the corrosion of the metal that can be used as the internal parts of the above-mentioned metal layer and portable electronic devices can be suppressed, and the cohesion (such as heat-resistant cohesion) is improved, so that the adhesion with the internal components of the portable electronic devices is more excellent.

[0097] The content of the above-mentioned rust inhibitor in the above-mentioned adhesive layer is preferably 0.2 mass parts or more, more preferably 0.5 mass parts or more, further preferably 1 mass parts or more, further preferably 1.5 mass parts or more, further preferably 4 mass parts or more, and particularly preferably 6 mass parts or more relative to the total amount of 10 mass parts of the carboxyl group-containing monomer and / or anhydride monomer that can be included in the monomer component constituting the above-mentioned acrylic polymer. If the above-mentioned content is 0.2 mass parts or more, the corrosion of the metal can be further suppressed. From the viewpoint of preferably taking into account the effect of suppressing metal corrosion and maintaining the performance of the internal components, the above-mentioned content can be, for example, 30 mass parts or less, 20 mass parts or less, 15 mass parts or less, 10 mass parts or less, 5 mass parts or less, or 3 mass parts or less. In particular, the content of the azole-based rust inhibitor is preferably within the above range.

[0098] The adhesive layer preferably contains a crosslinking agent. By containing a crosslinking agent, for example, the acrylic polymer in the acrylic adhesive layer can be crosslinked to control the gel fraction. The crosslinking agent can be used alone or in combination of two or more.

[0099] The cross-linking agent is not particularly limited, and examples thereof include isocyanate cross-linking agents, epoxy cross-linking agents, melamine cross-linking agents, peroxide cross-linking agents, urea cross-linking agents, metal alkoxide cross-linking agents, metal chelate cross-linking agents, metal salt cross-linking agents, carbodiimide cross-linking agents, oxazoline cross-linking agents, aziridine cross-linking agents, amine cross-linking agents, hydrazine cross-linking agents, silicone cross-linking agents, and silane cross-linking agents (silane coupling agents).

[0100] The content of the crosslinking agent in the pressure-sensitive adhesive layer is not particularly limited, but is preferably 0.001 to 20 parts by mass, more preferably 0.01 to 15 parts by mass, and particularly preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the total amount of the base polymer.

[0101] The isocyanate crosslinking agent is a compound having an average of two or more isocyanate groups per molecule (polyfunctional isocyanate compound). Examples of the isocyanate crosslinking agent include aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, and the like.

[0102] Examples of the aliphatic polyisocyanates include 1,2-ethylene diisocyanate; tetramethylene diisocyanates such as 1,2-tetramethylene diisocyanate, 1,3-tetramethylene diisocyanate, and 1,4-tetramethylene diisocyanate; hexamethylene diisocyanates such as 1,2-hexamethylene diisocyanate, 1,3-hexamethylene diisocyanate, 1,4-hexamethylene diisocyanate, 1,5-hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, and 2,5-hexamethylene diisocyanate; 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, and lysine diisocyanate.

[0103] Examples of the alicyclic polyisocyanates include isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; cyclopentyl diisocyanates such as 1,2-cyclopentyl diisocyanate and 1,3-cyclopentyl diisocyanate; hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tetramethylxylene diisocyanate, and 4,4′-dicyclohexylmethane diisocyanate.

[0104] Examples of the aromatic polyisocyanates include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4′-diphenylmethane diisocyanate, 2,4′-diphenylmethane diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylether diisocyanate, 2-nitrodiphenyl-4,4′-diisocyanate, 2,2′-diphenylpropane-4,4′-diisocyanate, Isocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, naphthalene-1,4-diisocyanate, naphthalene-1,5-diisocyanate, 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, xylylene-1,4-diisocyanate, xylylene-1,3-diisocyanate, etc.

[0105] Examples of the isocyanate crosslinking agent include commercially available products such as trimethylolpropane / toluene diisocyanate adduct (trade name “CORONATE L”, manufactured by Tosoh Corporation), trimethylolpropane / hexamethylene diisocyanate adduct (trade name “CORONATE HL”, manufactured by Tosoh Corporation), and trimethylolpropane / xylylene diisocyanate adduct (trade name “TAKENATE D-110N”, manufactured by Mitsui Chemicals, Inc.).

[0106] It should be noted that the isocyanate crosslinking agent may not be used in the aqueous dispersion of the modified acrylic polymer produced by emulsion polymerization, and if necessary, a blocked isocyanate crosslinking agent may be used in order to facilitate the reaction with water.

[0107] When an isocyanate crosslinking agent is used as the crosslinking agent, the content of the isocyanate crosslinking agent is not particularly limited, but is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and further preferably 1.5 parts by mass or more, relative to 100 parts by mass of the total amount of the base polymer. The content is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, further preferably 5 parts by mass or less, and particularly preferably 3 parts by mass or less.

[0108] Examples of the epoxy crosslinking agent (polyfunctional epoxy compound) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and sorbitan. Sugar alcohol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. In addition, commercial products such as trade name "TETRAD C" (Mitsubishi Gas Chemical Co., Ltd.) can also be cited as the above-mentioned epoxy crosslinking agent.

[0109] When an epoxy crosslinking agent is used as the crosslinking agent, the content of the epoxy crosslinking agent is not particularly limited, but is preferably more than 0 part by mass and less than 1 part by mass, more preferably 0.001 to 0.5 part by mass, further preferably 0.002 to 0.2 part by mass, further preferably 0.005 to 0.1 part by mass, and particularly preferably 0.008 to 0.05 part by mass, relative to 100 parts by mass of the total amount of the base polymer.

[0110] As the above-mentioned peroxide-based crosslinking agent, any crosslinking agent can be used as long as it generates free radical active species due to heat and crosslinks the base polymer. However, considering workability and stability, it is preferred to use a peroxide with a 1-minute half-life temperature of 80 to 160°C, and it is more preferred to use a peroxide with a 1-minute half-life temperature of 90 to 140°C.

[0111] Examples of the peroxide crosslinking agent include di(2-ethylhexyl) peroxydicarbonate (1-minute half-life temperature: 90.6° C.), di(4-tert-butylcyclohexyl) peroxydicarbonate (1-minute half-life temperature: 92.1° C.), di-sec-butyl peroxydicarbonate (1-minute half-life temperature: 92.4° C.), tert-butyl peroxyneodecanoate (1-minute half-life temperature: 103.5° C.), tert-hexyl peroxypivalate (1-minute half-life temperature: 109.1° C.), tert-butyl peroxypivalate (1-minute half-life temperature: 110.3° C.), dilauroyl peroxide. (1 minute half-life temperature: 116.4℃), dioctanoyl peroxide (1 minute half-life temperature: 117.4℃), 1,1,3,3-tetramethylbutyl peroxide-2-ethylhexanoate (1 minute half-life temperature: 124.3℃), di(4-methylbenzoyl) peroxide (1 minute half-life temperature: 128.2℃), dibenzoyl peroxide (1 minute half-life temperature: 130.0℃), tert-butyl peroxyisobutyrate (1 minute half-life temperature: 136.1℃), 1,1-di(tert-hexylperoxide)cyclohexane (1 minute half-life temperature: 149.2℃), etc.

[0112] The half-life of the above-mentioned peroxide crosslinking agent is an index indicating the decomposition rate of peroxide, and refers to the time until the residual amount of peroxide reaches half. Regarding the decomposition temperature used to obtain the half-life at any time, the half-life time at any temperature is recorded in the product catalog of the manufacturer, etc., and is recorded in, for example, the "Organic Peroxide Product Catalog 9th Edition (May 2003)" of NOF Corporation, etc. It should be noted that, as a determination method for the residual peroxide decomposition amount after reaction treatment, it can be determined by, for example, HPLC (high performance liquid chromatography). More specifically, for example, about 0.2g of the adhesive after reaction treatment is taken out each time, immersed in 10ml of ethyl acetate, extracted with a shaker at 25°C for 3 hours at 120rpm, and left to stand at room temperature for 3 days. Then, 10ml of acetonitrile is added, shaken at 25°C for 30 minutes at 120rpm, and filtered using a membrane filter (0.45μm), and about 10μl of the extract obtained is injected into HPLC for analysis, so as to be able to be used as the amount of peroxide after reaction treatment.

[0113] When a peroxide-based crosslinking agent is used as the crosslinking agent, the content of the crosslinking agent is not particularly limited, but is preferably 2 parts by mass or less, more preferably 0.02 to 2 parts by mass, and even more preferably 0.05 to 1 part by mass, based on 100 parts by mass of the acrylic polymer.

[0114] In addition, as the above-mentioned cross-linking agent, an organic cross-linking agent and a polyfunctional metal chelate can also be used in combination. The polyfunctional metal chelate is formed by covalent bonding or coordination bonding of a polyvalent metal and an organic compound. As polyvalent metal atoms, Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, etc. can be listed. As atoms in organic compounds that are covalently bonded or coordinated, oxygen atoms can be listed, and as organic compounds, alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, ketone compounds, etc. can be listed.

[0115] As the above-mentioned cross-linking agent, it is preferred to include an isocyanate cross-linking agent. In addition, it is more preferred to include other cross-linking agents together with the isocyanate cross-linking agent. As the above-mentioned other cross-linking agent, an epoxy cross-linking agent is preferably used. If such a cross-linking agent is used, then through its combination with the above-mentioned acrylic polymer (especially with the above-mentioned preferred acrylic polymer), an adhesive layer with excellent adhesion can be made even if it is thin.

[0116] The adhesive layer may further contain additives such as a crosslinking accelerator, an antioxidant, a filler (organic filler, inorganic filler, etc.), a colorant (pigment, dye, etc.), an antioxidant, a plasticizer, a softener, a surfactant, an antistatic agent, a surface lubricant, a leveling agent, a light stabilizer, an ultraviolet absorber, an inhibitor, a granular material, a foil material, etc. as needed within the range that does not impair the effect of the present invention. The above additives may be used alone or in combination of two or more.

[0117] The above-mentioned adhesive layer preferably does not substantially contain conductive particles such as metal powder, and the content is preferably 5 mass% or less, more preferably 2 mass% or less, further preferably 1 mass% or less, and particularly preferably 0.5 mass% or less, relative to 100 mass% of the total amount of the above-mentioned adhesive layer.

[0118] The thickness of the adhesive layer is not particularly limited, and is preferably 1 to 90 μm, more preferably 3 to 50 μm, further preferably 5 to 30 μm, and particularly preferably 10 to 30 μm. When the adhesive sheet is a double-sided adhesive sheet, the thickness of the adhesive layer is the thickness of the adhesive layer on the single-sided side. If the thickness is 1 μm or more, the adhesion of the adhesive sheet becomes higher. If the thickness is 90 μm or less, the thickness of the adhesive sheet can be further reduced.

[0119] The ratio of the thickness of the above-mentioned adhesive layer to the thickness of the above-mentioned substrate layer [adhesive layer / substrate layer] is not particularly limited, and is preferably 0.05 to 1.0, more preferably 0.07 to 0.6, and further preferably 0.08 to 0.5. When the thickness of the above-mentioned adhesive sheet is less than 100 μm, if the above-mentioned ratio is greater than 0.05, the adhesive layer can more fully exert its close adhesion, and its close adhesion with the internal components of the portable electronic device is better. If the above-mentioned ratio is less than 1.0, the thickness of the metal layer in the substrate layer is thicker, and the electromagnetic wave shielding performance in the low-frequency region is better. It should be noted that when the above-mentioned adhesive sheet is a double-sided adhesive sheet, the thickness of the above-mentioned adhesive layer is the thickness of the adhesive layer on the single-sided side. In addition, the thickness of the above-mentioned adhesive sheet is as described later.

[0120] The method for preparing the adhesive layer is not particularly limited, and examples thereof include applying (coating) an adhesive (adhesive composition) containing the base polymer on the substrate layer or release liner, and drying and curing the obtained adhesive composition layer; applying (coating) the adhesive composition on the substrate layer or release liner, and irradiating the obtained adhesive composition layer with active energy rays to cure it. In addition, heating and drying may be further performed as required.

[0121] Examples of the active energy rays include ionizing radiation such as α rays, β rays, γ rays, neutron rays, and electron rays; ultraviolet rays, and ultraviolet rays are particularly preferred. In addition, the irradiation energy, irradiation time, irradiation method, etc. of the active energy rays are not particularly limited.

[0122] The adhesive composition can be prepared by a known or customary method. For example, a solvent-based adhesive composition can be prepared by mixing an additive into a solution containing the base polymer as required. When the base polymer is the acrylic polymer, for example, an active energy ray-curable adhesive composition can be prepared by mixing an additive into a mixture of monomer components constituting the acrylic polymer or a partial polymer thereof as required.

[0123] It should be noted that the adhesive composition can be applied by a known coating method, such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a knife coater, a spray coater, a comma coater, a direct coater, or other coating machine.

[0124] The heat drying temperature of the solvent-based adhesive composition is preferably 40 to 200° C., more preferably 50 to 180° C., and further preferably 70 to 170° C. The drying time can be any appropriate time, for example, 5 seconds to 20 minutes, preferably 5 seconds to 10 minutes, and more preferably 10 seconds to 5 minutes.

[0125] When the acrylic adhesive layer is formed by active energy ray irradiation, the adhesive layer can be formed while the acrylic polymer is produced from the monomer components. The monomer components can be partially polymerized to form a slurry before the active energy ray irradiation. Ultraviolet irradiation can be performed using a high-pressure mercury lamp, a low-pressure mercury lamp, a metal halide lamp, etc.

[0126] The adhesive sheet can be manufactured according to a known or customary manufacturing method. The adhesive sheet can be obtained by directly forming the adhesive layer on the surface of the substrate layer (direct method), or by temporarily forming the adhesive layer on a release liner and then transferring (laminating) it to the substrate layer, thereby providing the adhesive layer on the substrate layer (transfer method).

[0127] The total thickness of the adhesive sheet is 100 μm or less (e.g., 5 to 100 μm), preferably 80 μm or less (e.g., 10 to 80 μm), and more preferably 60 μm or less (e.g., 15 to 60 μm). It should be noted that in this specification, the "total thickness of the adhesive sheet" refers to: for a single-sided adhesive sheet, the thickness from the surface of the substrate layer on which the adhesive layer is not provided to the adhesive surface of the adhesive layer; for a double-sided adhesive sheet, the thickness from the adhesive surface of one adhesive layer across the substrate layer to the adhesive surface of the other adhesive layer, excluding the thickness of the printed layer and the thickness of the release liner described later.

[0128] The electric field shielding effect of the pressure-sensitive adhesive sheet at a frequency of 100 kHz to 1000 kHz measured by the KEC method is 20 dB or more, preferably 25 dB or more.

[0129] The magnetic field wave shielding effect of the above-mentioned adhesive sheet at a frequency of 100kHz to 1000kHz measured by the KEC method is 5dB or more, preferably 5.5dB or more. If the electric field wave shielding effect at the above frequency is 20dB or more and the magnetic field wave shielding effect is 5dB or more, the electromagnetic wave shielding performance in the low-frequency region of the adhesive sheet is excellent. The higher the above-mentioned electric field wave shielding effect and the above-mentioned magnetic field wave shielding effect, the higher the electromagnetic wave shielding performance in the low-frequency region, and the upper limit is not particularly limited.

[0130] The adhesive force of the adhesive sheet relative to the PET film is not particularly limited, and is preferably 5N / 25mm or more, more preferably 10N / 25mm or more, and further preferably 15N / 25mm or more. If the above-mentioned adhesive force is 5N / 25mm or more, the adhesion to the internal components of the portable electronic device is excellent, and it is not easy to peel off even when the internal components are heated. It should be noted that the higher the above-mentioned adhesive force, the more preferred, and the upper limit is not particularly limited. In addition, the above-mentioned adhesive force is a value measured under the conditions of a temperature of 23°C, a peeling angle of 180°, and a peeling speed of 300mm / minute. It should be noted that when the above-mentioned adhesive sheet is a double-sided adhesive sheet, it is preferred that the adhesive force of at least one adhesive layer (especially the adhesive layer at least attached to one side of the internal components of the portable electronic device) is within the above range.

[0131] The time until the metal layer changes color under the conditions of 65°C and 90% RH is visually confirmed to be preferably 200 hours or more, more preferably 500 hours or more. This adhesive sheet has excellent corrosion resistance to the metal layer and the internal components of the portable electronic device. It should be noted that when the adhesive sheet is a double-sided adhesive sheet, it is preferred that at least one adhesive layer (especially the adhesive layer on at least one side of the internal components of the portable electronic device), especially the adhesive layers on both sides, meet the above performance.

[0132] The adhesive sheet may have other layers in addition to the substrate layer and the adhesive layer. As the other layers, for example, a black layer may be cited. For example, when the adhesive sheet is a single-sided adhesive sheet, the black layer is disposed on the surface of the substrate layer on the side where the adhesive layer is not disposed, and when the adhesive sheet is a double-sided adhesive sheet, the black layer is disposed on the side where the adhesive layer is disposed and on the surface of the two surfaces of the substrate layer facing the outside of the portable electronic device. When a black layer is disposed, it is preferably disposed on the entire surface of the substrate layer from the viewpoint of appearance design.

[0133] The black layer includes all layers showing black, and generally refers to a layer containing a black colorant. * a * b * Brightness L specified by the color system * The surface is shown as 40 or less (for example, 35 or less, preferably 30 or less). When the above-mentioned black layer is included, an excellent appearance is obtained when it is attached to a graphite plate. In particular, when the glossiness value of the surface of the substrate layer is low (for example, the glossiness value at 60° is 10 or less) and the light transmittance of the adhesive sheet is low (for example, 12 to 30%), a more excellent appearance can be obtained. It should be noted that the above-mentioned L * a * b *The color system is based on the regulations recommended by the International Commission on Illumination in 1976 or the regulations of JIS Z 8729. The black layer is preferably a black printed layer provided on the surface of the base material layer, for example.

[0134] The black layer preferably contains a black colorant and a binder. As the binder, materials known in the field of coatings or printing can be used. Examples thereof include polyurethane, phenolic resin, epoxy resin, urea-melamine resin, polymethyl methacrylate, etc. It should be noted that the black layer may contain white pigments such as titanium dioxide, zinc white, lead white, and other colorants, or may substantially contain no colorant other than the black colorant.

[0135] As the above-mentioned black colorant, an organic or inorganic colorant (pigment, dye, etc.) can be used. As the black colorant, carbon black, acetylene black, graphite, copper oxide, manganese dioxide, aniline black, perylene black, titanium black, cyanine black, activated carbon, ferrite, magnetite, chromium oxide, iron oxide, molybdenum disulfide, chromium complex, anthraquinone colorant, etc. can be listed. Among them, carbon black is preferred. Only one black colorant can be used, or two or more can be used. As the above-mentioned black colorant, there is no particular limitation, and it is preferred to use, for example, carbon black of 10nm to 500nm (preferably 10nm to 120nm). It should be noted that the above-mentioned average particle size represents the particle size (50% volume average particle size; D50) when the cumulative value in the particle size distribution measured by a particle size distribution measuring device based on a laser scattering / diffraction method is 50%.

[0136] The content ratio of the black colorant in the black layer is set according to the required hue, texture, etc., and is not particularly limited, but is, for example, 1% by mass or more, preferably 2% by mass or more, more preferably 5% by mass or more, and further preferably 15% by mass or more, relative to the total amount 100% by mass of the black layer. In addition, the content ratio of the black colorant is, for example, 65% by mass or less, and from the viewpoint of excellent finished product inspection, it is preferably 30% by mass or less, more preferably 15% by mass or less, and further preferably 8% by mass or less.

[0137] The thickness of the black layer is, for example, 0.1 μm or more, preferably 0.5 μm or more, more preferably 0.7 μm or more, further preferably 0.8 μm or more, and particularly preferably 1 μm or more. In addition, the thickness of the black layer is, for example, 10 μm or less, preferably 7 μm or less, more preferably 5 μm or less, further preferably 3 μm or less, and particularly preferably 2 μm or less. When the black layer is multilayer, the thickness of the black layer is the thickness of the multilayer as a whole. In addition, when the black layer is multilayer, the thickness of each black layer is, for example, preferably about 0.5 μm to 2 μm.

[0138] The black layer can be formed by applying a black layer forming composition to the substrate layer. Examples of the black layer forming composition include solvent-based, ultraviolet curable, and thermosetting types. The black layer can be formed by any known means used in the formation of the black layer. Preferably, a method of forming a black layer (black printed layer) by printing, for example, by gravure printing, flexographic printing, offset printing, etc. can be used. Among them, gravure printing is particularly preferred. The hue of the black layer can be adjusted relatively easily by controlling the gravure printing plate.

[0139] The black layer may be a single layer or a multilayer. When the black layer is a multilayer, it may be formed by, for example, repeatedly applying (e.g., printing) a black layer-forming composition. The types and amounts of the colorant and binder contained in each black layer may be the same or different.

[0140] The above-mentioned adhesive sheet can be provided with a release liner on the surface (adhesive face) of the adhesive layer until use. It should be noted that each adhesive face when the above-mentioned adhesive sheet is a two-sided adhesive sheet can utilize two release liners to protect respectively, and it is also possible to utilize 1 release liner that forms the release face on both sides to protect in a rolled-up form (winding body). The release liner is used as a protective material for the adhesive layer and is peeled off when it is attached to the adherend. It should be noted that it is also possible not to provide a release liner.

[0141] As the above-mentioned release liner, conventional release paper etc. can be used, which is not particularly limited, and for example, a substrate with a release treatment layer, a low adhesive substrate formed by a fluoropolymer, a low adhesive substrate formed by a non-polar polymer, etc. can be listed. As the substrate with the above-mentioned release treatment layer, for example, plastic films, paper, etc. that have been surface-treated using release treatment agents such as silicone, long-chain alkyl, fluorine, and molybdenum sulfide can be listed. As the fluorine-based polymer in the low adhesive substrate formed by the above-mentioned fluoropolymer, for example, polytetrafluoroethylene, polytrifluorochloroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc. can be listed. In addition, as the above-mentioned non-polar polymer, for example, olefin resins (such as polyethylene, polypropylene, etc.) can be listed. It should be noted that the release liner can be formed by a known or conventional method. In addition, the thickness of the release liner is not particularly limited either. In addition, in this specification, the release liner is considered to be not included in the adhesive sheet.

[0142] The adhesive sheet is used to fix the internal components of the portable electronic device. As the portable electronic device, for example, a portable phone, a smart phone, a tablet-type personal computer, a notebook-type personal computer, various wearable devices (for example, a wrist-wearable type worn on the wrist like a wristwatch; an assembled type worn on a part of the body with the help of a clip or a belt; an eye-wearing type including a glasses type (monocular type, binocular type. Also includes a head-fixed type.); a clothing type installed on a shirt, socks, hat, etc. in the form of an accessory; an ear-wearing type mounted on the ear like an earphone, etc.), a digital camera, a digital video camera, an audio device (a portable music player, an IC recorder, etc.), a computer (a calculator, etc.), a portable game device, an electronic dictionary, an electronic notebook, an electronic book, an in-vehicle information device, a portable radio, a portable TV, a portable printer, a portable scanner, a portable modem, etc. It should be noted that in this specification, "portable" is not sufficient to simply be able to be carried, and it refers to a level of portability that an individual (a standard adult) can carry relatively easily. The pressure-sensitive adhesive sheet is used in a manner such that the pressure-sensitive adhesive layer is closely attached to the internal member of the portable electronic device. The internal member is a member that is not exposed to the outside of the portable electronic device when the portable electronic device is in use.

[0143] The adhesive surface of the adhesive sheet is particularly preferably pasted on a metal component (such as SUS, aluminum, copper, etc.) in the portable electronic device. The metal component is preferably used for light shielding. In addition, when the adhesive sheet is a two-sided adhesive sheet, one adhesive surface of the adhesive sheet can be pasted on a metal component in the portable electronic device, and the other adhesive surface can be pasted on, for example, a graphite plate. When the other adhesive surface is pasted on the graphite plate, the heat generated in the portable electronic device can be effectively released to the outside.

[0144] Example

[0145] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples at all.

[0146] Example 1

[0147] Into a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet tube, a reflux condenser and a dropping funnel, 95 parts by mass of butyl acrylate (BA) and 5 parts by mass of acrylic acid (AA) as monomer components and 233 parts by mass of ethyl acetate as a polymerization solvent were added, and stirred for 2 hours while introducing nitrogen. After removing oxygen in the polymerization system by this operation, 0.2 parts by mass of 2,2'-azobisisobutyronitrile was added as a polymerization initiator, and solution polymerization was carried out at 60°C for 8 hours to obtain a solution of an acrylic polymer. The Mw of the acrylic polymer was about 70×10 4 .

[0148] To the acrylic polymer solution, 0.8 parts by mass of 1,2,3-benzotriazole (trade name “BT-120”, manufactured by Johoku Chemical Industry Co., Ltd.), 20 parts by mass of a tackifier resin (trade name “YS POLYSTER S-145”, softening point of about 145° C., hydroxyl value of 70 to 110 mgKOH / g, manufactured by Yasuhara Chemical Co., Ltd.), 2 parts by mass of an isocyanate crosslinking agent (trade name “CORONATE L”, 75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation) and 0.01 parts by mass of an epoxy crosslinking agent (trade name “TETRAD-C”, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, manufactured by Mitsubishi Gas Chemical Co., Ltd.) were added with stirring and mixed to prepare an adhesive composition.

[0149] The PSA composition was applied to the release surface of a 38 μm thick polyester release liner (trade name “DIAFOIL MRF”, manufactured by Mitsubishi Chemical Corporation) and dried at 100° C. for 2 minutes to form a 15 μm thick PSA layer.

[0150] Next, a copper foil (35 μm thick) as a substrate was attached to the exposed surface of the adhesive layer obtained above at room temperature using a laminator.

[0151] Example 2

[0152] A pressure-sensitive adhesive sheet of Example 2 was prepared in the same manner as in Example 1, except that the pressure-sensitive adhesive layer had a thickness of 5 μm and a copper plate (thickness of 50 μm) was used as the substrate.

[0153] Example 3

[0154] A pressure-sensitive adhesive sheet of Example 3 was prepared in the same manner as in Example 1, except that the pressure-sensitive adhesive layer had a thickness of 4 μm and an aluminum foil (thickness of 12 μm) was used as the substrate.

[0155] Example 4

[0156] A pressure-sensitive adhesive sheet of Example 4 was prepared in the same manner as in Example 1 except that a silver foil (thickness: 35 μm) was used as the substrate.

[0157] Example 5

[0158] A pressure-sensitive adhesive sheet of Example 5 was prepared in the same manner as in Example 1, except that the pressure-sensitive adhesive layer had a thickness of 5 μm and an iron plate (thickness of 50 μm) was used as the substrate.

[0159] Example 6

[0160] Into a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet tube, a reflux condenser and a dropping funnel, 30 parts by mass of 2-ethylhexyl acrylate (2EHA), 70 parts by mass of ethyl acrylate (EA), 5 parts by mass of methyl methacrylate (MMA) and 4 parts by mass of 2-hydroxyethyl acrylate (EHA) as monomer components and 233 parts by mass of ethyl acetate as a polymerization solvent were added, and stirred for 2 hours while introducing nitrogen. After removing oxygen in the polymerization system by such operation, 0.2 parts by mass of 2,2'-azobisisobutyronitrile was added as a polymerization initiator, and solution polymerization was carried out at 60°C for 8 hours to obtain a solution of an acrylic polymer. The Mw of the acrylic polymer is about 90×10 4 .

[0161] To the acrylic polymer solution, 8.5 parts by mass of an isocyanate crosslinking agent (trade name "CORONATE L", manufactured by Tosoh Corporation) was added as a crosslinking agent based on 100 parts by mass of the acrylic polymer contained in the solution, and the mixture was stirred and mixed to prepare a pressure-sensitive adhesive composition.

[0162] The PSA composition was applied to the release surface of a 38 μm thick polyester release liner (trade name “DIAFOIL MRF”, manufactured by Mitsubishi Chemical Corporation) and dried at 100° C. for 2 minutes to form a 15 μm thick PSA layer.

[0163] Next, a copper foil (35 μm thick) as a substrate was attached to the exposed surface of the adhesive layer obtained above at room temperature using a laminator.

[0164] Example 7

[0165] A PSA sheet of Example 7 was prepared in the same manner as in Example 1 except that 1,2,3-benzotriazole (trade name "BT-120", manufactured by Johoku Chemical Industry Co., Ltd.) was not blended when preparing the PSA composition.

[0166] Example 8

[0167] 0.07 parts of a photopolymerization initiator (trade name "IRGACURE 184" and trade name "IRGACURE 651" manufactured by BASF were used in a mass ratio of 1:1) was added to a monomer mixture consisting of 66 parts by mass of 2-EHA, 15 parts by mass of N-vinyl-2-pyrrolidone (NVP), and 18 parts by mass of HEA, and the mixture was irradiated with ultraviolet rays until the viscosity reached about 20 Pa·s to obtain a prepolymer composition in which part of the above-mentioned monomer components were polymerized. Next, 20 parts by mass of a terpene phenol resin (trade name “YS POLYSTER S-145”, manufactured by Yasuhara Chemical Co., Ltd.) as a tackifier resin, 18 parts by mass of an oligomer of dicyclopentanyl methacrylate (DCPMA) and methyl methacrylate (MMA) (copolymer composition: DCPMA / MMA=60 / 40), 0.01 parts by mass of an epoxy crosslinking agent (trade name “TETRAD-C”, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 0.25 parts by mass of hexane diacrylate (HDDA), 0.3 parts by mass of a silane coupling agent (trade name “KBM-403”, manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.2 parts by mass of 1,2,3-benzotriazole (trade name “BT-120”, manufactured by Johoku Chemical Co., Ltd.) were added to 100 parts by mass of the prepolymer composition and mixed to obtain an adhesive composition (pre-cured composition).

[0168] The above-mentioned adhesive composition was coated on a polyethylene terephthalate (PET) release liner (trade name "MRF50", manufactured by Mitsubishi Chemical Corporation) so that the final thickness (thickness of the adhesive layer) was 15 μm, and the coating layer was covered with a PET release liner (trade name "MRF38", manufactured by Mitsubishi Plastics Corporation) to block oxygen, and then irradiated for 300 seconds at an illumination intensity of 5 mW / cm 2 The adhesive layer was cured by ultraviolet rays, thereby obtaining a 15 μm thick adhesive layer protected by release liners on both sides.

[0169] Next, one release liner was peeled off to expose the adhesive surface of the adhesive layer, and a copper foil (35 μm thick) as a substrate was attached to the exposed surface of the adhesive layer obtained above at room temperature using a laminator.

[0170] Comparative Example 1

[0171] A pressure-sensitive adhesive sheet of Comparative Example 1 was prepared in the same manner as in Example 1 except that a graphite plate (thickness: 30 μm) was used as the substrate.

[0172] Comparative Example 2

[0173] A PSA sheet of Comparative Example 2 was prepared in the same manner as in Example 1 except that the thickness of the PSA layer was 10 μm and an aluminum foil (thickness 5 μm) was used as the substrate.

[0174] Comparative Example 3

[0175] A PSA sheet of Comparative Example 3 was prepared in the same manner as in Example 1 except that the thickness of the PSA layer was 5 μm and a PET film (thickness 50 μm) was used as the substrate.

[0176] <Evaluation>

[0177] The following evaluations were performed on the pressure-sensitive adhesive sheets obtained in the Examples and Comparative Examples.

[0178] (1) Electric field wave shielding effect and magnetic field wave shielding effect

[0179] A square of 150 mm square is cut out from the adhesive sheet obtained by the embodiment and the comparative example as an evaluation sample. Next, in the electromagnetic wave shielding effect measuring device, between the receiving side fixture and the sending side fixture set opposite to each other, a substance obtained by clamping the above-mentioned evaluation sample from both sides of the receiving side fixture and the sending side fixture using steel wool arranged in two well shapes is placed. The receiving side fixture and the sending side fixture present a structure that is symmetrically divided in a plane perpendicular to the direction of its transmission axis. In the KEC method, first, the signal output from the spectrometer is input to the sending side fixture by means of an attenuator. And, after the signal received by the receiving side fixture and passed through the attenuator is amplified by a preamplifier, the signal level is measured by the spectrometer. It should be noted that the spectrometer outputs the attenuation when the evaluation sample is set in the electromagnetic wave shielding effect measuring device, taking the state where the evaluation sample is not set in the electromagnetic wave shielding effect measuring device as a reference. Using this apparatus, the electromagnetic shielding properties, that is, the electric field shielding effect and the magnetic field shielding effect were measured at 100 kHz to 1000 kHz at a temperature of 23°C.

[0180] (2) Adhesion

[0181] From the adhesive sheet obtained by the embodiment and the comparative example, a size of 25mm in width × 100mm in length was cut out to make a measurement sample. In addition, as an adherend, a PET film (trade name "LUMIRROR S10", manufactured by Toray) with a thickness of 50μm was prepared to be fixed to a stainless steel plate with a double-sided adhesive tape. In addition, under an environment of 23°C and 50%RH, a 2kg roller was moved back and forth once to press the adhesive surface of the above-mentioned measurement sample onto the surface of the above-mentioned adherend (the surface of the PET film). Thereafter, after being placed under the same environment for 30 minutes, a universal tensile compression tester (trade name "tensile compression tester TG-1kN", manufactured by MINEBEAMITSUMI) was used, and according to JIS Z0237:2009, the peel strength (N / 25mm) was measured under the conditions of a tensile speed of 300mm / min and a peeling angle of 180° as the adhesive force.

[0182] [Table 1]

[0183]

[0184] (3) Corrosion resistance

[0185] [Corrosion test]

[0186] A transparent PET film with a thickness of 200 μm was pasted on the adhesive surface of the adhesive sheet obtained by the embodiment for backing, and cut into a square shape of 10 mm square, thereby preparing a laminate sample having a structure of PET film / adhesive sheet / substrate layer. The sample was stored under high temperature and humidity conditions of 85°C and 85% RH. After 500 hours from the beginning of storage, the substrate layer was visually observed through the PET film, and the presence or absence of appearance changes was evaluated by the following three stages. As a result, for Examples 1 to 6 and 8, no discoloration was observed in the observation after 500 hours, and it was evaluated as excellent in corrosion resistance.

Claims

1. A pressure-sensitive adhesive sheet comprising a substrate layer and a pressure-sensitive adhesive layer provided on at least one surface of the substrate layer, The substrate layer comprises a metal layer of 10 to 80 μm, When the metal layer is a copper layer, the thickness of the metal layer is 30 to 60 μm. The total thickness of the adhesive sheet is 100 μm or less, The electric field wave shielding effect measured by the KEC method at a frequency of 100kHz to 1000kHz is 20dB or more. The magnetic field wave shielding effect measured by the KEC method at a frequency of 100kHz to 1000kHz is 5dB or more. The adhesive layer comprises an acrylic polymer, The content ratio of the acrylic polymer in the pressure-sensitive adhesive layer exceeds 50% by mass relative to 100% by mass of the total amount of the pressure-sensitive adhesive layer. The acrylic polymer contains butyl (meth)acrylate as a monomer component in an amount of 50% by mass or more relative to the total amount of all monomer components, The acrylic polymer comprises a structural unit derived from a carboxyl group-containing monomer and / or a structural unit derived from an acid anhydride monomer, and the proportion of the carboxyl group-containing monomer and / or the acid anhydride monomer in 100% by weight of the total amount of all monomer components constituting the acrylic polymer is 3 to 7% by weight. The adhesive layer is substantially free of conductive particles. The adhesive sheet is used for fixing internal components of portable electronic devices.

2. The adhesive sheet according to claim 1, wherein The adhesive layer includes a tackifying resin and the acrylic polymer.

3. The adhesive sheet according to claim 1 or 2, wherein The adhesive layer includes an azole-based rust inhibitor, and the content of the azole-based rust inhibitor is less than 8 parts by mass based on 100 parts by mass of the total amount of the acrylic polymer.

4. The adhesive sheet according to claim 3, wherein The azole-based rust inhibitor includes at least one benzotriazole-based compound selected from the group consisting of 1,2,3-benzotriazole, 5-methylbenzotriazole, 4-methylbenzotriazole, and carboxybenzotriazole.

5. The adhesive sheet according to claim 1 or 2, wherein The ratio of the thickness of the adhesive layer to the thickness of the substrate layer, that is, adhesive layer / substrate layer, is 0.05 to 1.

0.

6. The adhesive sheet according to claim 1 or 2, wherein The adhesive layer is bonded to a metal component inside the portable electronic device.

Citation Information

Patent Citations

  • Acrylic adhesives and its production method

    JP2002069411A

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A

  • Conductive adhesive sheet and electronic device

    WO2015076174A1

  • Electroconductive pressure-sensitive adhesive tape

    CN101809105A

  • Pressure-sensitive adhesive composition and pressure-sensitive adhesive tape

    CN107636106A